PENERAPAN GREEN COMPUTING PADA KUISIONER INSTRUMEN PENILAIAN KINERJA DOSEN DI POLITEKNIK NEGERI SUBANG - Nunu Nugraha Purnawan (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
The lecturer's performance assessment by students in the form of an online Lecturer Performance Assessment Instrument Questionnaire (KIPKD) is in line with the work concepts of Green Computing by utilizing computer hardware and software better, more efficiently and more useful. KIPKD online POLSUB uses Google Forms, because it has an attractive and responsive look, provides a fairly complete choice of stuffing model, free, the results are neatly arranged and can be analyzed easily. This research method uses literature review in the form of books, journals that discuss about topics related to the use of Google Forms as a medium in the manufacture of questionnaires for surveys and data collection, as well as related to the concept of Green Computing. While data collection methods used in field research by way of observation of the system running in the academic POLSUB. The use of KIPKD online illustrates that POLSUB participates in preserving the environment, with no 12 paper/year rims, equivalent to 12 tree trunks.